The Magic Egg, and Other Stories - Stockton, Frank R., 1834-1902 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Magic Egg, and Other Stories" by Frank R. Stockton is a collection of short stories likely written during the late 19th century. The stories delve into themes of wonder, adventure, and human nature, often woven through fantastical elements and engaging narratives. The story begins with Herbert Loring, a young man gathering friends for a theatrical exhibition where he showcases magical acts, including a fascinating display involving a magic egg that seemingly brings a chick to life. At the start of "The Magic Egg," Loring is set to entertain a select audience at a private club theatre. He begins with a display of colorful fireworks, which captivates the audience, though his true intent is revealed with the magic egg. He hypnotizes the entire audience without their knowledge, leading them to believe in the reality of the magical performance. This opening sets the stage for a deeper exploration of themes like perception, reality, and the dynamics of illusion, particularly as Edith Starr, Loring$1 (Bs betrothed, discovers the truth behind the spectacle and challenges Loring$1 (Bs manipulation of reality. As the curtain falls on this initial act, readers are left to ponder the moral implications of Loring's experiment and the nature of belief itself. (This is an automatically generated summary.)s
The magic egg -- His wife's deceased sister -- The widow's cruise -- Captain Eli's best ear -- Love before breakfast -- The staying power of Sir Rohan -- A piece of red calico -- The Christmas wreck -- My well and what came out of it -- Mr. Tolman -- My unwilling neighbor -- Our archery club.
Release date is 1996-02-01
Keywords: Short stories; United States -- Social life and customs -- 19th century -- Fiction